Posisi Perempuan dalam Kewarisan Adat Jambi Indonesia - Hidayati, Rahmi; Ramlah, Ramlah; Maryani, Maryani; Prawira, Ilham Abdi; Asiyah, Asiyah (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2024)
This research aims to determine women’s position in the distribution of inheritance in the Merangin Jambi community. This research uses social and legal research methods  to understand legal phenomena from the social and cultural context in which the law exists. The primary data for this research comes from in-depth interviews with religious and traditional leaders. In contrast, secondary data is obtained from relevant literature.. The data  is then analyzed through editing, organizing and grouping research results. The research  result In the Merangin Jambi custom, women are the place where men’s families return when they are in trouble or disaster. This can be seen in the dominant  position of women in the distribution of  inheritance. There is no difference in principles between men and women in the distribution of inheritance, they have the same rights with consideration of the common good.